Self-Management Open Online Trials in Health (SMOOTH): Methods and public involvement survey of corresponding authors of existing online trials - Price, A; Vasanthan, L; Clarke, M; Liew, S; Brice, A; Burls, A (University of Buckingham Press, 2018)
Background The Self-Management Open Online Trials in Health (SMOOTH) survey reports methods as well as researcher preferences in online trials and explores to what extent public and participant involvement in online trials occurs. This survey queried researchers’ experience in online trials and their perceived value of public and patient research involvement. The preparation, consideration, and publication of research involvement require the use of resources by the authors. The survey explores whether authors consider resources to be sufficient or useful to improve online trials about self-management of health. Objective To identify the present state of public research involvement in online trials concerning health self-management and to explore the needs of researchers when contemplating the building and writing up an online trials protocol. Methods The ORCID database of online trials was used to survey corresponding authors concerning trial methods and preferences including the frequency, format, and quality of citizen involvement in online trials about health self-management. Results Blended trials were reported as online trials. Remote recruitment and communications were less common than local recruitment even when participants signed up online. Research volunteers helped more with recruitment and as advisors than with trial design, analysis, or outcome setting. Forty-seven percent of Corresponding authors report that an online trial was the best way of answering their research question. Conclusions Detailed reporting of online methods and volunteer researcher involvement was hindered by role confusion between research volunteers and trial participants. Respondents were responsive to the development of protocol and reporting suggestions but were not in favor of adopting complex new frameworks that require extensive time, training, space, and funding.